A multifunctional ionic hydrogel, strain sensor and flexible all-solid-state supercapacitor and preparation method and application thereof
By using P(AM-co-AA)/Trehalose/LiCl ionic hydrogel and flexible CNTs/MXene-loaded flexible electrodes, a high-performance strain sensor and flexible all-solid-state supercapacitor were assembled, which solved the problems of poor tensileability and insufficient stability in traditional equipment, and achieved high sensitivity and long-life detection and energy storage effects.
Patent Information
- Application Number
- CN202310157816.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-02-23
AI Technical Summary
Existing flexible strain sensors have poor tensile properties and poor compatibility between conductive fillers and elastomers, making it difficult to achieve high tensile properties, high sensitivity and biocompatibility. At the same time, traditional supercapacitors have shortcomings in flexibility and stability.
Using P(AM-co-AA)/Trehalose/LiCl ionic hydrogel, a multifunctional ionic hydrogel with superstretchability, high conductivity and anti-freeze moisturizing properties was prepared through the combined action of trehalose and lithium chloride. The hydrogel is used to assemble strain sensors and flexible all-solid supercapacitors, combined with flexible electrodes loaded with CNTs/MXene to form a supercapacitor with a sandwich structure.
It realizes a strain sensor with high sensitivity and a large detection range, can accurately detect human movement, and the flexible all-solid supercapacitor has high specific capacitance, excellent capacitance retention, good mechanical stability and excellent anti-freeze characteristics, which are suitable for powering electronic devices.
Smart Images

Figure CN116333379B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible wearable sensors, and in particular relates to a multifunctional ionic hydrogel, a strain sensor and a flexible all-solid-state supercapacitor, and a preparation method and application thereof. Background Art
[0002] In recent years, various wearable electronic devices that integrate communication technology, the Internet of Things, artificial intelligence, and virtual reality and can collect, process, and transmit information have developed rapidly. Among them, flexible strain sensors have attracted extensive research attention due to their huge application potential in human motion detection, soft robots, human-computer interaction, and artificial skin. Usually, a combination of elastomers and conductive fillers is used to make strain sensors. However, traditional strain sensors usually have problems such as poor stretchability and poor compatibility between conductive fillers and elastomers. Therefore, it is still a challenge to develop strain sensors with high stretchability, high sensitivity, and biocompatibility. In addition, in order to ensure the long-term continuous operation of wearable electronic devices, the demand for developing portable, flexible, and safe energy storage devices is becoming more and more urgent. Supercapacitors used in flexible wearable electronic devices are a new type of energy storage device and are widely studied because of their advantages of high power density, short charging time, long service life, and high safety. Electrodes and electrolytes are key components of supercapacitors, and making electrodes and electrolytes flexible is the key to manufacturing flexible supercapacitors.
[0003] Conductive hydrogel is a functional hydrogel that combines a hydrogel matrix with a conductive filler. Ionic conductive hydrogel is an important component of conductive hydrogel. A large number of free ions are introduced into the three-dimensional polymer network of the hydrogel as conductive fillers, which gives the ionic hydrogel excellent conductivity. Multifunctional ionic hydrogels with high mechanical properties, high conductivity, self-adhesion, antifreeze and moisturizing properties are ideal for preparing strain sensors. The porous microstructure, high ionic conductivity and solid-like structural stability of ionic hydrogels make them ideal electrolyte materials for flexible all-solid-state supercapacitors. Therefore, the rational design of multifunctional hydrogels is an effective way to simultaneously obtain high-performance strain sensors and flexible all-solid-state supercapacitors. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a multifunctional ionic hydrogel, a strain sensor and a flexible all-solid-state supercapacitor and their preparation methods and applications, which respectively realize human motion signal detection and power supply for electronic devices. The present invention prepares P(AM-co-AA) / Trehalose / LiCl ionic hydrogel, which has super stretchability, high conductivity, good adhesion and excellent antifreeze and moisturizing properties. The assembled hydrogel strain sensor has high sensitivity and a large strain detection range. Applying the strain sensor to human motion detection can realize sensitive and accurate detection of various human motions such as joint bending, facial expressions, and swallowing. A high-performance flexible all-solid-state supercapacitor is assembled by using polyester fiber fabric loaded with CNTs / MXene as a flexible electrode and ionic hydrogel as a hydrogel electrolyte. The supercapacitor has a large specific capacitance, excellent capacitance retention, good deformation electromechanical stability and excellent antifreeze properties.
[0005] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a multifunctional ionic hydrogel, wherein the hydrogel is a P(AM-co-AA) / Trehalose / LiCl ionic hydrogel, trehalose is rich in hydroxyl groups, and forms quasi-covalent hydrogen bonds with polar groups on polymer chains. Under the action of covalent quasi-hydrogen bonds, polymer chains are interconnected through trehalose, and at the same time, dangling chains in the polymer network are repaired. Trehalose makes the hydrogel super stretchable, and the combined action of trehalose and lithium chloride makes the hydrogel self-adhesive and antifreeze and moisturizing. Lithium chloride makes the hydrogel have high ionic conductivity, and the surface structure of the hydrogel is a porous structure, which is conducive to ion migration.
[0006] A method for preparing an ionic hydrogel, the preparation steps comprising:
[0007] (1) dissolving trehalose in deionized water and stirring to prepare a uniform trehalose solution;
[0008] (2) adding anhydrous lithium chloride to the trehalose solution in step (1) and stirring to prepare a lithium chloride / trehalose mixed solution;
[0009] (3) taking the lithium chloride / trehalose mixed solution in step (2), adding acrylamide, acrylic acid, N,N′-methylenebisacrylamide and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the mixed solution, and vigorously stirring until a transparent uniform solution is formed;
[0010] (4) pouring the mixed solution obtained in step (3) into a silicone mold, and then polymerizing it under ultraviolet light to form an ionic hydrogel.
[0011] Furthermore, in steps (1) and (2), the concentration of trehalose is 30 wt % and the concentration of lithium chloride is 20 wt %.
[0012] Furthermore, in the step (3), the mass ratio of acrylamide (AM), acrylic acid, N,N′-methylenebisacrylamide and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone is 2000:106:1.4:66;
[0013] Or, in step (4), the UV lamp is 10W and the reaction time is 1h.
[0014] A strain sensor based on ionic hydrogel, wherein the ionic hydrogel is prepared into a strip shape, wires are inserted into both ends of the ionic hydrogel as electrodes, and the electrodes are packaged with VHB tape to ensure a tight bond between the electrodes and the hydrogel.
[0015] Furthermore, the sensing principle of the sensor is: lithium chloride provides a large number of dissociated ions to the polymer network, stretching destroys the porous three-dimensional structure of the hydrogel, reduces the ion transmission path, and increases the resistance of the hydrogel. At the same time, stretching increases the length of the hydrogel and reduces the cross-sectional area, resulting in an increase in the resistance of the hydrogel. Based on these two mechanisms, the hydrogel strain sensor has good strain sensitivity.
[0016] An application of an ionic hydrogel strain sensor, wherein the strain sensor is used for human motion detection, detecting joint bending, blinking, frowning, smiling, and swallowing signals.
[0017] A flexible all-solid-state supercapacitor based on ionic hydrogel is prepared by depositing CNTs / MXene on polyester fabric by dip coating, and the ionic hydrogel is used as the electrolyte to assemble a flexible all-solid-state supercapacitor with a sandwich structure.
[0018] A method for preparing a flexible all-solid-state supercapacitor based on ionic hydrogel, the preparation steps comprising:
[0019] (1) preparing a CNTs suspension and a MXene suspension into a mixed solution (m / m = 1:1);
[0020] (2) immersing the polyester fiber fabric washed with deionized water into the mixed solution in step (2), leaving it in the solution for 1 minute, then taking it out and drying it under vacuum at 35° C.;
[0021] (3) Repeating the polyester fiber fabric in step (2) three times to prepare a flexible electrode;
[0022] (4) Adhere conductive silver cloth to both ends of the fabric electrode in step (3) and lead out as a current collector;
[0023] (5) attaching the fabric electrode and the current collector in (4) together with the ionic hydrogel to construct a flexible all-solid-state supercapacitor with a sandwich structure having symmetrical electrodes;
[0024] (6) Use VHB tape to encapsulate the flexible all-solid-state supercapacitor in (5).
[0025] An application of a flexible all-solid-state supercapacitor based on ionic hydrogel, wherein the flexible all-solid-state supercapacitor can power light-emitting diodes and electronic watches.
[0026] The benefits of the multifunctional ionic hydrogel, strain sensor and flexible all-solid-state supercapacitor of the present invention and their preparation methods and applications are as follows:
[0027] (1) The high-performance multifunctional ionic hydrogel prepared by the present invention has super stretchability (4529% strain) and high ionic conductivity (9.04S / m). At the same time, the ionic hydrogel has excellent self-adhesiveness and antifreeze and moisturizing properties.
[0028] (2) The present invention assembles a strain sensor based on the prepared ionic hydrogel, which has excellent sensing performance, achieves a large detection range (0-4200%) and high sensitivity (GF=3.59). The strain sensor is applied to human motion detection, achieving sensitive and accurate detection of various human motions.
[0029] (3) The present invention assembled a sandwich-type flexible all-solid-state supercapacitor based on the prepared ionic hydrogel and the flexible fabric electrode loaded with CNTs / MXene. The supercapacitor exhibited a thermal conductivity of 148.2 mF / cm 2 The supercapacitor has high specific capacitance, excellent cycle performance, outstanding mechanical stability and good low temperature resistance. The supercapacitor can be used to power light-emitting diodes (LEDs) and electronic watches. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a diagram of the synthesis mechanism of the ionic hydrogel prepared in Example 1 of the present invention;
[0031] Figure 2 Fourier transform infrared spectra (FTIR) of the P(AM-co-AA) hydrogel and P(AM-co-AA) / Trehalose hydrogel prepared in Example 1 of the present invention;
[0032] Figure 3 This is a SEM image of the ionic hydrogel prepared in Example 1 of the present invention;
[0033] Figure 4 The strain sensing mechanism of the strain sensor prepared in Example 2 of the present invention;
[0034] Figure 5 a is the relative resistance-strain response curve of the strain sensor prepared in Example 2 of the present invention;
[0035] Figure 5 b is the response / recovery time of the strain sensor prepared in Example 2 of the present invention when the strain is 50%;
[0036] Figure 5 c is the relative resistance response of the strain sensor prepared in Example 2 of the present invention under small strain;
[0037] Figure 5 d is the relative resistance response of the strain sensor prepared in Example 2 of the present invention under large strain;
[0038] Figure 5 e is the relative resistance response of the strain sensor prepared in Example 2 of the present invention under different strain rates;
[0039] Figure 5 f is the relative resistance response of the strain sensor prepared in Example 2 of the present invention under 1000 cycles of strain;
[0040] Figure 6 ad is the relative resistance response of the strain sensor prepared in Example 3 of the present invention when detecting the bending of human fingers, wrists, elbows and knees;
[0041] Figure 7 ad is the relative resistance response of the strain sensor prepared in Example 3 of the present invention when detecting frowning, blinking, smiling and swallowing of the human body;
[0042] Figure 8 This is a schematic diagram of assembling a flexible all-solid-state supercapacitor prepared in Example 4 of the present invention;
[0043] Fig. 9 a is the CV curve of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention at a scan rate of 5-100 mV / s;
[0044] Fig. 9 b is the GCD curve of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention at a current density of 0.5-2 mA / cm;
[0045] Fig.10 The area capacitance and coulombic efficiency of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention at different current densities calculated according to the GCD curve;
[0046] Fig.11 The relationship between energy density and surface power density of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention at different current densities;
[0047] Fig.12 This is the capacitance retention rate of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention after 3000 charge and discharge cycles. The inset is the GCD curve at intervals of 500 cycles.
[0048] Fig.13 a is the CV curve of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention under different bending states;
[0049] Fig.13 b is the GCD curve of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention under different bending states;
[0050] Fig.13 c is the CV curve of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention at room temperature, 5°C and -20°C;
[0051] Fig.13 d is the GCD curve of the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention at room temperature, 5°C and -20°C;
[0052] Fig.14 a is a flexible all-solid-state supercapacitor prepared in Example 4 of the present invention, which is used to power a light-emitting diode (LED).
[0053] Fig.14 b shows the flexible all-solid-state supercapacitor prepared in Example 4 of the present invention for powering the electronic watch. DETAILED DESCRIPTION
[0054] The specific implementation manner will be further described below in conjunction with the accompanying drawings.
[0055] Embodiment 1:
[0056] A high-performance multifunctional ionic hydrogel is prepared by a simple one-pot method. Trehalose is rich in hydroxyl groups and can form quasi-covalent hydrogen bonds with many polar groups on the polymer chain. Under the action of covalent hydrogen bonds, the polymer chains can be interconnected through trehalose, and the dangling chains in the polymer network can also be repaired. The addition of trehalose makes the hydrogel super stretchable. The combined effect of trehalose and lithium chloride makes the hydrogel self-adhesive and antifreeze and moisturizing. Lithium chloride makes the hydrogel have high ionic conductivity. The surface structure of the hydrogel is a porous structure, which is conducive to ion migration.
[0057] A method for preparing an ionic hydrogel:
[0058] The hydrogel synthesis mechanism is shown in the figure Figure 1As shown, trehalose is dissolved in deionized water and stirred to prepare a trehalose solution with a mass fraction of 30%, and then anhydrous lithium chloride is added to the trehalose solution (30wt%) and stirred to prepare a lithium chloride / trehalose mixed solution with a lithium chloride mass fraction of 20%. Take 7mL of lithium chloride / trehalose mixed solution, add 1.9936g acrylamide (AM), 0.106g acrylic acid (AA), 1.36mg N,N′-methylenebisacrylamide (MBAA) and 0.0662g 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959) to the mixed solution, and stir vigorously until a transparent uniform solution is formed. The obtained mixed solution is poured into a silica gel mold, and then polymerized under ultraviolet light (10W) for 1h to form an ionic hydrogel. The hydrogel synthesis mechanism diagram is shown in Figure 1 shown.
[0059] Characterization and analysis of ionic hydrogels:
[0060] Figure 2 Fourier transform infrared (FTIR) spectra of P(AM-co-AA) hydrogel and P(AM-co-AA) / Trehalose hydrogel.
[0061] The P(AM-co-AA) hydrogel shows a 3369 cm- -1 The characteristic peak of C=O appears at 1711cm -1 The characteristic peaks of NH stretching vibration and C=O stretching vibration of P(AM-co-AA) / Trehalose hydrogel shifted to 3359 cm -1 and 1670cm -1 This is due to the formation of intermolecular hydrogen bonds between trehalose and P(AM-co-AA) chains.
[0062] The surface morphology and microstructure of the ionic hydrogels were characterized by scanning electron microscopy.
[0063] Figure 3 SEM image of ionic hydrogel.
[0064] The porous structure of ionic hydrogel is conducive to the transmission of ions and improves the ionic conductivity of the hydrogel.
[0065] Embodiment 2:
[0066] A strain sensor based on ionic hydrogel is prepared into a strip shape, wires are inserted into both ends of the hydrogel as electrodes, and the hydrogel is packaged with VHB tape to ensure a tight bond between the electrode and the hydrogel.
[0067] The sensing principle of strain sensor based on ionic hydrogel is:
[0068] Figure 4 The strain sensing mechanism of the sensor is shown. Lithium chloride provides a large number of dissociated ions to the polymer network. Stretching destroys the porous three-dimensional structure of the hydrogel, reduces the transmission path of ions, and increases the resistance of the hydrogel. At the same time, stretching increases the length of the hydrogel and reduces the cross-sectional area, resulting in an increase in the resistance of the hydrogel. Based on these two mechanisms, the hydrogel strain sensor has good strain sensitivity.
[0069] Performance test of strain sensor based on ionic hydrogel:
[0070] In order to study the performance of the hydrogel strain sensor, the sensing characteristics of the sensor were tested using a computer control system consisting of Agilent (Keysight 34470A) and a tensile testing machine (TM2101-T5). To evaluate the sensitivity of the sensor, the sensitivity of the strain sensor is defined as the specification factor (GF), which is the ratio of the relative resistance change (ΔR / R0) to the strain ε. The calculation formula is as follows. GF = (ΔR / R0) / ε, where ΔR is the change in resistance with strain, R0 is the initial resistance before strain, and ε is the applied strain. In order to verify whether the strain sensor can be stably applied in the field of human motion detection for a long time, the dynamic performance of the sensor device needs to be tested, so the response and recovery time, large and small strain stretching, different speed stretching, and long-term stability of the strain sensor were tested.
[0071] The gauge factor was calculated based on the slope of the relative resistance change (ΔR / R0) and strain (ε). Figure 5 As shown in (a), the GF is 0.55 in the strain range of 0–750%, increases to 1.46 in the strain range of 750–2200%, and reaches as high as 3.59 in the strain range of 2200–4200%. Figure 5 b shows the response / recovery time of the sensor. In order to check the response time of the sensor to external deformation, a 50% strain was applied to the strain sensor at a rate of 1000 mm / min, and the strain was unloaded at the same rate after holding for 10 seconds. It was observed that the strain sensor had a response / recovery time of 0.41 / 0.68 s. This proves that this hydrogel strain sensor can respond to external strain almost immediately. In order to study the detection range of the hydrogel strain sensor, the strain sensor was tested with small strain and large strain respectively to evaluate the reliability and repeatability of the sensing performance under different working conditions. Figure 5c, d show the relative resistance response of the sensor to small strain and large strain, respectively. The relative resistance of the strain sensor produced a fast and distinguishable response to small strain (1%, 3%, 5% and 10%) and large strain (100%, 200%, 300% and 400%), and the relative resistance remained stable and reliable during repeated loading-unloading of the same strain. This shows that the sensor has excellent strain recognition ability and repeatability, while the extremely low detection limit and large detection range make it very suitable for the detection of various types of human motion. Figure 5 e shows the relative resistance change curves obtained by stretching the strain sensor at 30mm / min, 60mm / min, 90mm / min, and 120mm / min in the same time. The sensor device remains stable and has good repeatability under different stretching speeds, which shows that the strain sensor can adapt to fast and slow strain changes in practical applications. In order to further study the long-term stability of the strain sensor, 100% strain is repeatedly loaded / unloaded to detect the relative resistance change of the strain sensor. Figure 5 f shows the relative resistance response of the sensor under 1000 cycles of strain. The change in its response value is almost constant during 1000 repeated stretching / releasing tests. The resistance value of the strain sensor at the beginning and end of the experimental test hardly changes, which indicates that the strain sensor has high durability and long-term stability.
[0072] Embodiment 3:
[0073] An application of a strain sensor, the strain sensor can be applied to human body motion signal detection.
[0074] Figure 6 It shows that sensors are installed on various joints to recognize various violent human movements.
[0075] like Figure 6 As shown in a, the hydrogel strain sensor is tied to the finger joint and identifies the bending of the finger (0°, 30°, 60° and 90°) by recording the change in relative resistance. It is worth noting that once the stress is released, the relative resistance quickly drops back to its initial value. Figure 6 b, c show that the hydrogel strain sensor can detect wrist and elbow movements. When detecting wrist bending, the strain sensor showed a clear and repeatable response under multiple bending and release cycles. This shows that the hydrogel sensor has high stability. When detecting elbow bending, the relative resistance increases with the bending angle, which shows that the sensor can detect different ranges of motion of the same joint. In addition, Figure 6d shows the strain sensor mounted on the knee joint to accurately track strenuous movements such as walking and running. As the speed of movement increases, the response curve becomes denser, and the sensor also shows good responsiveness and repeatability.
[0076] Figure 7 It shows that sensors are mounted on the surface of the skin to recognize various fine human movements.
[0077] Figure 7 AC shows the sensors fixed on the forehead, corners of the eyes and corners of the mouth of volunteers to monitor fine muscle movements close to the skin. The sensors produced obvious and distinguishable relative resistance responses to frowning, blinking and smiling, which means that the hydrogel sensors have the potential to be applied as emotion monitors to detect emotional expressions. Figure 7 d shows the hydrogel strain sensor attached to the throat to detect the tiny but complex muscle movements during swallowing. When the volunteers performed periodic swallowing movements, the relative resistance response was seen to exhibit the same characteristic waveform.
[0078] Embodiment 4:
[0079] A flexible all-solid-state supercapacitor based on ionic hydrogel is prepared by depositing CNTs / MXene on polyester fabric by dip coating, and the ionic hydrogel is used as the electrolyte to assemble a flexible all-solid-state supercapacitor with a sandwich structure.
[0080] A method for preparing a flexible all-solid-state supercapacitor based on ionic hydrogel:
[0081] First, the CNTs aqueous suspension and the MXene suspension were configured into a mixed solution (m / m=1:1). The polyester fiber fabric washed with deionized water was immersed in the CNTs / MXene mixed solution, placed in the solution for 1 minute, taken out and dried under vacuum at 35°C, and the operation was repeated three times to obtain a flexible electrode. Then, the conductive silver cloth was adhered to both ends of the fabric electrode and led out as a current collector, and the fabric electrode and the current collector were attached to the ionic hydrogel to construct a flexible all-solid-state supercapacitor with a sandwich structure of symmetrical electrodes. Finally, the flexible all-solid-state supercapacitor was encapsulated using VHB tape. Figure 8 A schematic diagram of the flexible all-solid-state supercapacitor assembly is shown.
[0082] Performance test of flexible all-solid-state supercapacitor based on ionic hydrogel:
[0083] The electrochemical performances of the assembled supercapacitors were evaluated by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and cycling stability measurements in a two-electrode system.
[0084] Fig. 9 a shows the CV curves of the supercapacitor at scan rates from 5 to 100 mV / s. The CV curves show an approximately rectangular shape and mirror symmetry, which is mainly attributed to the electronic double-layer capacitance. Fig. 9 b shows the GCD curves of the supercapacitor at different current densities. The GCD curves present a linear profile and an isosceles triangle, which indicates that a typical reversible charging and discharging process occurs at the interface between the electrolyte and the electrode. Fig.10 The area capacitance and coulombic efficiency of the supercapacitor at different current densities calculated from the GCD curve are shown. 2 When the area capacitance reaches 148.2mF / cm 2 Although the area capacitance decreases with the increase of current density, at 2.0 mA / cm 2 The current density still maintains 130.9mF / cm 2 The area capacitance of the supercapacitor is 2.0 mA / cm2, indicating that the supercapacitor has excellent electrochemical performance at higher current density. In addition, the Coulombic efficiency gradually increases with the increase of current density. 2 It reached 95.9%. Fig.11 The relationship between the surface energy density and the surface power density at different current densities is shown. 2 The surface power density is 20.04μWh / cm 2 The high areal energy density is worth noting, at 0.96 mW / cm 2 The energy density remains at 16.29μWh / cm 2 High value. By 1mA / cm 2 The cycling performance of the supercapacitor was evaluated by 3000 charge / discharge cycles at the same current density. Fig.12 As shown, the GCD curve at intervals of 500 cycles has always maintained the shape of an isosceles triangle, but shows a shorter charge and discharge time as the number of cycles increases. After 3000 charge and discharge cycles, the capacitance retention rate still remains at about 84.2%, indicating that the supercapacitor has excellent cycle stability and long-term durability. The flexibility and mechanical reliability of the supercapacitor were evaluated by measuring the CV curves and GCD curves at different bending angles. Fig.13 a, b show the CV curves and GCD curves of the supercapacitor at different bending angles. When the supercapacitor is bent from 0° to 45°, 90°, 135° and 180°, the CV curve and GCD curve deviate slightly from the original curve. When the bending angle is 180°, the area capacitance does not decrease significantly compared with the initial value. These results show that bending has no significant effect on the electrochemical performance of the supercapacitor. Fig.13c, d show the CV curves and GCD curves of the supercapacitor after being placed at 5 and -20 ° C for 12 hours. The CV curves at 5 and -20 ° C deviate from the initial shape at room temperature. At the same time, the GCD curve at low temperature shows a larger voltage drop and a shorter charge and discharge time. This is because the migration rate of ions at low temperatures is limited. However, the GCD curve at low temperature still maintains an approximately triangular shape and still has 85.9 mF / cm at -20 ° C. 2 The high area capacitance and capacitance retention rate reached 61.3%, which indicates that the supercapacitor has excellent anti-freezing property.
[0085] Flexible all-solid-state supercapacitors based on ionic hydrogel electrolytes and textile electrodes have excellent electrochemical properties, ideal flexibility and outstanding low-temperature resistance.
[0086] An application of a flexible all-solid-state supercapacitor, which can be used to power electronic devices. Fig.14 a, b show that the flexible all-solid-state supercapacitor can power a light-emitting diode (LED) and an electronic watch. This indicates that supercapacitors have broad application prospects in wearable and flexible electronics.
Claims
1. A multifunctional ionic hydrogel, characterized in that: The preparation steps include: (1) dissolving trehalose in deionized water and stirring to prepare a uniform trehalose solution; (2) adding anhydrous lithium chloride to the trehalose solution in step (1) and stirring to prepare a lithium chloride / trehalose mixed solution; (3) taking the lithium chloride / trehalose mixed solution in step (2), adding acrylamide, acrylic acid, N,N′-methylenebisacrylamide and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the mixed solution, and vigorously stirring until a transparent uniform solution is formed; (4) pouring the mixed solution obtained in step (3) into a silicone mold, and then polymerizing it under ultraviolet light to form an ionic hydrogel.
2. The method for preparing the ionic hydrogel according to claim 1, characterized in that: The preparation steps include: (1) dissolving trehalose in deionized water and stirring to prepare a uniform trehalose solution; (2) adding anhydrous lithium chloride to the trehalose solution in step (1) and stirring to prepare a lithium chloride / trehalose mixed solution; (3) taking the lithium chloride / trehalose mixed solution in step (2), adding acrylamide, acrylic acid, N,N′-methylenebisacrylamide and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the mixed solution, and vigorously stirring until a transparent uniform solution is formed; (4) pouring the mixed solution obtained in step (3) into a silicone mold, and then polymerizing it under ultraviolet light to form an ionic hydrogel.
3. The method for preparing the ionic hydrogel according to claim 2, characterized in that: In the steps (1) and (2), the concentration of trehalose is 30 wt % and the concentration of lithium chloride is 20 wt %.
4. The method for preparing the ionic hydrogel according to claim 2, characterized in that: In the step (3), the mass ratio of acrylamide (AM), acrylic acid, N,N′-methylenebisacrylamide and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone is 2000:106:1.4:66; Or, in step (4), the UV lamp is 10W and the reaction time is 1h.
5. A strain sensor based on ionic hydrogel, the sensor comprising the ionic hydrogel according to claim 1, or the ionic hydrogel contained in the sensor is prepared by the method according to any one of claims 2 to 4, characterized in that: The ionic hydrogel was prepared into strips, wires were inserted into both ends of the ionic hydrogel as electrodes, and they were packaged with VHB tape to ensure a tight bond between the electrodes and the hydrogel.
6. The strain sensor based on ionic hydrogel according to claim 5, characterized in that: The sensing principle of the sensor is: lithium chloride provides a large number of dissociated ions for the polymer network, stretching destroys the porous three-dimensional structure of the hydrogel, reduces the ion transmission path, and increases the resistance of the hydrogel. At the same time, stretching increases the length of the hydrogel and reduces the cross-sectional area, resulting in an increase in the resistance of the hydrogel. Based on these two mechanisms, the hydrogel strain sensor has good strain sensitivity.
7. An application of a strain sensor based on the ionic hydrogel according to any one of claims 5 to 6, characterized in that: The strain sensor is used for human motion detection, detecting joint bending, blinking, frowning, smiling, and swallowing signals.
8. A flexible all-solid-state supercapacitor based on ionic hydrogel, the supercapacitor comprising the ionic hydrogel according to claim 1, or the electrolyte in the supercapacitor is prepared according to the method according to any one of claims 2 to 4, characterized in that: CNTs / MXene were deposited on polyester fabric by dip coating to prepare flexible electrodes, and ionic hydrogel was used as electrolyte to assemble a flexible all-solid-state supercapacitor with a sandwich structure.
9. A method for preparing a flexible all-solid-state supercapacitor based on ionic hydrogel according to claim 8, characterized in that: The preparation steps include: (1) preparing a CNTs suspension and a MXene suspension into a mixed solution (m / m = 1:1); (2) immersing the polyester fiber fabric washed with deionized water into the mixed solution in step (2), leaving it in the solution for 1 minute, then taking it out and drying it under vacuum at 35° C.; (3) Repeating the polyester fiber fabric in step (2) three times to prepare a flexible electrode; (4) Adhere conductive silver cloth to both ends of the fabric electrode in step (3) and lead out as a current collector; (5) attaching the fabric electrode and the current collector in (4) together with the ionic hydrogel to construct a flexible all-solid-state supercapacitor with a sandwich structure having symmetrical electrodes; (6) Use VHB tape to encapsulate the flexible all-solid-state supercapacitor in (5).
10. The use of the flexible all-solid-state supercapacitor based on ionic hydrogel according to claim 8, characterized in that: The flexible all-solid-state supercapacitor can power light-emitting diodes and electronic watches.
Citation Information
Patent Citations
Hydrogel flexible strain sensor and preparation method thereof
CN111234112A
Telescopic anti-freezing full-physical crosslinked hydrogel material for multi-mode flexible sensor and preparation method thereof
CN111548513A
Cited By
Layer-by-layer stacked structure fabric electrode and preparation method thereof
CN121416330A